2016
DOI: 10.3945/ajcn.116.134403
|View full text |Cite
|
Sign up to set email alerts
|

Zinc carnosine works with bovine colostrum in truncating heavy exercise–induced increase in gut permeability in healthy volunteers

Abstract: ZnC, taken alone or with colostrum, increased epithelial resistance and the TJ structure and may have value for athletes and in the prevention of heat stroke in military personnel. This trial was registered at www.isrctn.com as ISRCTN51159138.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
97
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 65 publications
(119 citation statements)
references
References 24 publications
(35 reference statements)
13
97
0
3
Order By: Relevance
“…In a similar manner to previously reported findings (Davison et al 2016; Marchbank et al 2011), we observed an increase in intestinal permeability (as measured by urinary L/R ), following strenuous exercise which was blunted by 14 days of oral Col supplementation (acting as a positive control). The main findings of this study are (1) the exercise-induced change in urinary L/R was paralleled by an increase in plasma I-FABP, (2) the exercise-induced increases in urinary L/R and plasma I-FABP were both blunted by 14 days of oral Col supplementation.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In a similar manner to previously reported findings (Davison et al 2016; Marchbank et al 2011), we observed an increase in intestinal permeability (as measured by urinary L/R ), following strenuous exercise which was blunted by 14 days of oral Col supplementation (acting as a positive control). The main findings of this study are (1) the exercise-induced change in urinary L/R was paralleled by an increase in plasma I-FABP, (2) the exercise-induced increases in urinary L/R and plasma I-FABP were both blunted by 14 days of oral Col supplementation.…”
Section: Discussionsupporting
confidence: 92%
“…The use of urinary L/R as a method of assessing intestinal permeability following exercise has previously been shown in this exercise model (Davison et al 2016; Marchbank et al 2011). The use of the same mixture of L/R (which also includes mannitol to maintain consistency and osmolality) through a series of studies (Davison et al 2016; Mahmood et al 2007; Marchbank et al 2008, 2011; Playford et al 2001) allows reliable comparisons of the effects of exercise on intestinal barrier permeability to be made.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations